Increasing The Brand Awareness of KONOPA to Its Customers through Instagram Account Management - Maichel Perdana Korompis (Institute of Research and Community Outreach - Petra Christian University, 2021)
KONOPA or Komunitas Noken Papua is an official trade brand registered by the Papua Legal Department and Human Rights Department since 2011 located in Jayapura, Papua. KONOPA's main product is Noken, a multifunctional knotted or woven bag of Papuan. Unlike other online-based Noken sellers, KONOPA has its own production space in making Noken. However, I found that there was a lack of audience interaction in KONOPA’s social media activity as well as the problem. After conducting an interview, the customers mostly were not interested in discovering the information KONOPA provided. Therefore, it is necessary to update the ways in promoting in order to increase consumer engagement. Thus, I designed some Instagram content and display pictures. These works would be beneficial for the organization to draw back the customers’ attention and buy the products. Based on the final result as well as the solved problem, the average number of the audience interaction has increased.Keywords: Brand awareness, Social Media Management, Instagram, Consumer Engagement